Analysis of information systems strategic planning using ward and peppard framework case e-commerce company - Johanes Fernandes Andry; Devi Yurisca Bernanda; Honni Honni; Kevin Christianto; Agustina Andriani (International Journal of Advances in Applied Sciences, 2023)
The e-commerce industry which is developing significantly is always required to be able to adapt well to technological developments where information systems/information technologies (IS/IT) strategic planning must be further developed to support the company's business processes. In this research, the authors focus on analyzing how the information systems strategic planning is currently underway at an e-commerce company. The author uses the ward and peppard framework to analyze the business environment and IS/IT environment internally and externally. Many methods have been developed within the framework such as strengths, weaknesses, opportunities and threats (SWOT) analysis which focus on exposure the company's internal and external conditions, McFarlan strategic grid focus on assessing the overall contribution of IS/IT, and its impact on business success, from both a strategic, and operational perspective, value chain focus on optimizing technology, and business applications, political, economic, social, and technological (PEST) analysis focus on considerations of legal, political, economic, social, and technological developments, critical success factor (CSF) analysis focus on product quality priorities, customer service, product prices, company resources, and technology used. The results of the analysis of these methods are the results of this study, namely the results of portfolio application recommendations for the next four years which can be used as a reference for companies to develop their business strategic planning systems.